Evaluation of a new cryptococcal antigen lateral flow immunoassay in serum, cerebrospinal fluid and urine for the diagnosis of cryptococcosis: a meta-analysis and systematic review. - Hua-Rong Huang; Li-Chao Fan; Bhavana Rajbanshi; Jin-Fu Xu (PLoS ONE)
Background A new lateral flow immunoassay (LFA) for the detection of cryptococcal antigen was developed. Objective We aimed to systematically review all relevant studies to evaluate the diagnostic accuracy of the cryptococcal antigen LFA on serum, CSF and urine specimens. Methods We searched public databases including PubMed, Web of Science, Elsevier Science Direct and Cochrane Library for the English-language literature published up to September 2014. We conducted meta-analyses of sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR) and diagnostic odds ratios (DOR) and SROC of LFA in serum and CSF, respectively. The sensitivity of LFA in urine was also analyzed. Subgroup analyses were carried out to analyze the potential heterogeneity. Results 12 studies were included in this study. The pooled sensitivity and specificity values of LFA in serum were 97.6% (95% CI, 95.6% to 98.9%) and 98.1% (95% CI, 97.4% to 98.6%), respectively. The average PLR of LFA in serum was 43.787 (95% CI, 22.60-84.81) and the NLR was 0.03 (95% CI, 0.01-0.09). The pooled DOR was 2180.30 (95% CI, 868.92-5471.00) and the AUC was 0.9968. The pooled sensitivity and specificity values of LFA in CSF were 98.9% (95% CI, 97.9% to 99.5%) and 98.9% (95% CI, 98.0% to 99.5%), respectively. The average PLR of LFA in serum was 48.83 (95% CI, 21.59-110.40) and the NLR was 0.02 (95% CI, 0.01-0.04). The pooled DOR was 2931.10 (95% CI, 1149.20-7475.90) and the AUC was 0.9974. The pooled sensitivity value of LFA in urine was 85.0% (95% CI, 78.7% to 90.1%). Conclusions The study demonstrates a very high accuracy of LFA in serum and CSF for the diagnosis of cryptococcosis in patients at risk. LFA in urine can be a promising sample screening tool for early diagnosis of cryptococcosis.